Determination of cyanamide residue in 21 plant-derived foods by liquid chromatography-tandem mass spectrometry. (15th January 2018) - Cheng, Cheng; Di, Shanshan; Zhang, Wenjun; Chen, Li; Tian, Zhongnan; Zhou, Zhiqiang; Diao, Jinling
Highlights: A method for detecting cyanamide in 21 plant-derived foods was developed. The method is simple, sensitive, and widely applicable. This method has good accuracy and precision. Abstract: Cyanamide is widely used in agriculture, and has a modest toxicity in humans. In the present study, a simple, sensitive, and widely applicable method for detecting cyanamide in 21 plant-derived foods was developed. In the proposed method, after the samples were homogenized and extracted, the method employs clean-up with multi-walled carbon nanotubes (MWCNTs) and derivatization with dansyl chloride. The derivatized sample extracts were quantified with liquid chromatography-tandem mass spectrometry (LC-MS/MS). The mean recoveries were in the range of 67.4%–107.1%, and the RSDs were between 1.0% and 17.8%. The quantification limit in shiitake‬, green tea and chinese pepper was 0.05 mg/kg, and in others 18 plant-derived foods was 0.01 mg/kg. Among the data of 5 different laboratories, the repeatability limits (r) ranged from 0.0010 to 0.0941, and the reproducibility limits (R) ranged from 0.0031 to 0.2667. Moreover, the repeatability among different testing personnels in the same laboratory also has been examined.